Estimation of Free Acid Content and the Effect of Thermal Treatments on HMF Levels in Samples from the Local Market in Derna, Libya - Maqboulah Almasouri,; Anwaigy Almasawri, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted on five types of honey available in the local market in the city of Derna, including Dryas honey extracted from the plant Thapsia garganica. Caper honey, extracted from the plant Capparis spinosa L., Sidr honey, extracted from the plant Ziziphus lotus, Zaater honey, extracted from the plant Thymus compactus, and Rabie honey is extracted from various plants during the spring season. The content and effects of thermal treatments on hydroxymethylfurfural (HMF) were evaluated, and the conformity of local honey to the Libyan Standard Specification Law No. 281 of 1988 was verified through spectral and quantitative analyses of the studied samples. Using White's method, which is based on measuring in the UV range at two wavelengths (284 nm, 336 nm) using a 6305 UV/VIS spectrophotometer, the results of the study showed that the free acid content recorded the highest value for Sidr honey, with a value of 31.16 mg/kg. HMF values were less than 40 mg/kg. HMF values exceeded the permissible values of 40 mg/kg after three hours of heat treatment at 40°C, 65°C, and 70°C, respectively, in almost all samples. The most affected samples by heat treatment were thyme, and the least affected was spring honey.